2023
DOI: 10.1371/journal.pgph.0001662
|View full text |Cite
|
Sign up to set email alerts
|

Estimates and trends of zero vegetable or fruit consumption among children aged 6–23 months in 64 countries

Abstract: Children require a diverse diet, that includes vegetables and fruits, to support growth and development and prevent non-communicable diseases. The WHO-UNICEF established a new infant and young child feeding (IYCF) indicator: zero vegetable or fruit (ZVF) consumption among children aged 6–23 months. We estimated the prevalence, trends, and factors associated with ZVF consumption using nationally representative, cross-sectional data on child health and nutrition in low-and-middle-income countries. We examined 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 40 publications
3
10
2
Order By: Relevance
“…In a study conducted by Allen et al ( 28 ), it was found that a significant proportion of children (aged 6–23 months) residing in 64 developing countries, specifically 45.7%, do not include vegetables or fruits in their diet, indicating a prevalence of malnutrition in this population. In Pakistan, there has been a significant emergence and global spread of extensively drug-resistant S .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study conducted by Allen et al ( 28 ), it was found that a significant proportion of children (aged 6–23 months) residing in 64 developing countries, specifically 45.7%, do not include vegetables or fruits in their diet, indicating a prevalence of malnutrition in this population. In Pakistan, there has been a significant emergence and global spread of extensively drug-resistant S .…”
Section: Introductionmentioning
confidence: 97%
“…Typhi, particularly in recent years. It is worth noting that in 2018, approximately 65% of children in the country did not consume an adequate amount of vegetables or fruits, which was the highest across Asian countries, with India following closely ( 28 ). This correlation may be attributed to the association between the consumption of fruits and vegetables and the enhancement of immunity and antibacterial activity ( 26 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…After 6 months, children undergo rapid growth and development, for which breastmilk alone is inadequate. Thus, it’s fundamental to supplement breastfeeding with nutrient-dense, diversified diets that include fruits and vegetables ( 3 , 4 ). Zero vegetable or fruit consumption (ZVF), which is one of many elements of minimum dietary diversity (MDD), is a novel metric introduced by the United Nations Children’s Fund (WHO-UNICEF) to assess infant and young child feeding (IYCF).…”
Section: Introductionmentioning
confidence: 99%
“…Zero vegetable or fruit consumption (ZVF), which is one of many elements of minimum dietary diversity (MDD), is a novel metric introduced by the United Nations Children’s Fund (WHO-UNICEF) to assess infant and young child feeding (IYCF). ZVF measures the proportion of children between the ages of 6 and 23 months who have not consumed any vegetables or fruits in the 24 h prior to the query ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation